KOMPETENSI GURU DALAM PEMBELAJARAN MELALUI SUPERVISI EDUKATIF KOLABORATIF SECARA PERIODIK - Eka Herwira; Khamsir Khamsir (Program Studi PGSD FKIP Universitas Bung Hatta, 2022)
The teacher is one of the important components in the learning process, the teacher plays a role in creating a process of interaction in all directions between students, teachers and learning resources so that learning objectives are realized. Although the current learning system is no longer a teacher center, a teacher still plays an important role in guiding students. To improve the performance and insight of teachers in learning at SD Negeri 016/XI Talang Lindung, schools carry out action research related to the problems above. Due to the limitations of the researcher, this research is only focused on educative supervision, so the title of the action research is